Sodium salicylate effects on prostate cancer aggressiveness and development of prostate cancer spheroids for drug evaluation - RUISONG WANG (2019)
Prostate cancer (PCA) is one of the most common cancers in males’ affecting the genitourinary system. Although early stage PCA can be effectively treated, therapeutic options for patients with aggressive PCA are more limited and have lesser efficacy. In recent years, aspirin has been found to be an effective chemo-preventative treatment for a range of cancers. However, its mechanism of its action is not fully understood yet. Aspirin has shown great promise in PCA and is currently being employed in clinical trials. Thus, defining aspirin’s molecular impact on prostate cancer cells would provide valuable information to improve the clinical management of PCA patients. This thesis aimed to evaluate the consequence of aspirin exposure on cell cycle, proliferation and functional parameters of prostate cancer cells to determine aspirin’s mechanistic role in supporting the treatment of prostate cancer patients. This thesis also established a 3D culture system to enhance our standard in vitro models applied in the evaluation of drug efficacy and toxicity. The metabolite of aspirin, salicylate, was exposed to PC3 and DU145 prostate cancer cell, and PNT2, a normal prostate cell line. Cytotoxicity analysis based upon relative population doubling (RPD), Real-Time Quantitative Polymerase Chain Reaction (RT-qPCR) for gene expression profiling and INCell Analyzer 2000 analysis for cell morphological and DNA damage assessment, were used to evaluate the cellular impact of salicylate exposure. The role of the COX-2 signalling pathway in salicylate’s mode of action was considered by repeating salicylate exposure experiments in the presence of the inhibitor celecoxib; while activation of the NF-B pathway was also studied. To better understand the consequence of salicylate exposure on a human tumour, PC3 cell-spheroids were fabricated on agarose-coated 96 well-plates and were characterised by the MTT assay (cell viability), confocal microscopy (to assess necrosis, oxygen availability and morphology), and RT-qPCR for COX-2 expression. Salicylate was subsequently exposed to these spheroids and consequence of this treatment was established by comparing the experimental outcomes to the endpoints evaluated in 2D PC3 cell exposures. Salicylate was found to downregulate effects on growth and COX-2 gene expression; it induced morphological changes, DNA damage and cell mitochondria loss; delayed the cell cycle; and increased intracellular Ca2+ level. These effects were more prominent in the PCA cells than in PNT2 cells indicating that the cancer cells were more sensitive to salicylate toxicity than normal prostate cells. The role of salicylate in PCA was partially COX-2-dependent and NF-B-dependent. Although similar responses were noted when salicylate was exposed to PC3 cell spheroids, generally the level of response was lower than observed in the 2D PC3 cultures. The data contained within this thesis demonstrates that aspirin induces anti-cancer effects on PCA cells partially via NF-B and COX-2 mediated pathways. The 3D culture system provided an exciting and more realistic model for drug evaluation. Aspirin, therefore, has significant potential value for the clinician management of PCA patients.